2015
DOI: 10.1111/epi.12968
|View full text |Cite
|
Sign up to set email alerts
|

Early and chronic gray matter volume changes in limbic encephalitis revealed by voxel‐based morphometry

Abstract: SUMMARYObjective: Antibody-associated limbic encephalitis (LE) is an increasingly recognized cause of mostly adult-onset temporal lobe epilepsy. Magnetic resonance imaging (MRI) typically shows volume and signal changes of the mesiotemporal structures. However, recent studies indicate that imaging characteristics depend on the type of the associated antibody. The aim of the present study was to investigate early and chronic gray matter (GM) volume changes in LE by means of voxel-based morphometry (VBM). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
2
31
1
Order By: Relevance
“…This result aligns with other recent studies that have conducted comparable voxel-based morphometry analyses (Wagner et al , 2015; Finke et al , 2017). …”
Section: Resultssupporting
confidence: 92%
“…This result aligns with other recent studies that have conducted comparable voxel-based morphometry analyses (Wagner et al , 2015; Finke et al , 2017). …”
Section: Resultssupporting
confidence: 92%
“…In line with previous reports of this patient population (Dalmau and Rosenfeld, 2014;Miller et al, 2017), manual (blinded) segmentation of the hippocampi from high-resolution structural MRI scans confirmed that our patients showed volume loss confined to the left (Patients -HPC: 2506mm 3 (mean) +/-394 (standard deviation), control participants -CTL: 3173 mm 3 +/-339, W=4.0, p=0.002) and right (HPC: 2678mm 3 +/-528, CTL: 3286mm 3 +/-301, W=8.0, p=0.01) hippocampus. To rule out pathological differences between patients and controls elsewhere in the brain, an automated voxel-based-morphometry (VBM; Ashburner, 2009) analysis was carried out on whole brain T1 weighted MRI images and, in line with previous reports on patients of this sort (Wagner et al, 2015;Finke et al, 2017;Miller et al, 2017), did not result in any significant group differences outside of the hippocampus even at a liberal uncorrected p-value of less than 0.001. Neuropsychologically, the patients displayed an impairment in immediate and delayed recall on the Logical Memory (short stories) test (Wechsler, 1997), and they recollected significantly fewer episodic ('internal'), but not semantic ('external') details on the Autobiographical Interview , as detailed in Table 2.…”
Section: Participantsmentioning
confidence: 99%
“…Volume and signal changes of mesiotemporal structures are well‐known characteristics of LE on magnetic resonance imaging (MRI) and have been demonstrated by both conventional and postprocessing imaging studies . In contrast to these well‐known changes of the gray matter, the white matter usually does not show any abnormalities on routine clinical MRI examinations.…”
mentioning
confidence: 99%